ANALISIS KETIMPANGAN DISTRIBUSI GURU DAN DAMPAKNYA TERHADAP KOMPETENSI GURU SEKOLAH DASAR - Latifah, Revi; Aulia Rahman, Maulida; Nadiroti Muslihah, Neni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Quality education requires professional and competent teachers. However, the unequal distribution of teachers and the low competence of elementary school teachers remain significant challenges in Indonesia, particularly in disadvantaged, frontier, and outermost (3T) regions. This study aims to analyze the factors contributing to the unequal distribution of teachers and its impact on the competence of elementary school teachers. The method employed is a literature review by examining 15 relevant scientific articles published between 2020 and 2025, obtained from Google Scholar. Data were analyzed using a thematic analysis approach, including data reduction, data display, and conclusion drawing. The results indicate that the unequal distribution of teachers is caused by mismatches in academic qualifications, inadequate workforce planning, and limited incentives in remote areas. These conditions lead to low mastery of pedagogical, professional, social, and personal competencies. Therefore, policies based on competency-based teacher placement, continuous professional development, and strengthened monitoring and evaluation systems are necessary to improve the quality of basic education.